The rich tradition of jaguar research and conservation in Venezuela and its impact on human-jaguar coexistence throughout the species’ range: La rica tradición de investigación y conservación del jaguar en Venezuela y su impacto en la coexistencia entre humanos y jaguares en el área de distribución de la especie - Polisar, John; Hoogesteijn, Almira; Perera-Romero, Lucy; Puerto-Carrillo, María Fernanda; Isasi-Catalá, Emiliana; Jędrzejewski, Włodzimierz; Hoogesteijn, Rafael (Anartia, 2022)
Some of the earliest studies on jaguars and human-jaguar coexistence took place in Venezuela, including by Ambassador (to Kenya) Edgardo Mondolfi, a Cornell graduate (Animal Production and Zoology), professor at the Central University of Venezuela, Director of several Ministries, with links to the Smithsonian Institution, the Species Survival Commission of the IUCN, and the United Nations Environmental Program (UNEP). Mondolfi is considered the “father” of modern Mammalogy in Venezuela (Fig. 1). His mastery of all matters mammalian led to the mentoring of many researchers, amongst them two veterinarians, Rafael Hoogesteijn and Ernesto Boede. The three carved a place for Venezuela as jaguar studies started in the 1980s. Their chapter in the 1986 edited volume Cats of the World is testimony to that, one of the earliest serious publications on jaguars in the world (Mondolfi & Hoo-gesteijn 1986). Much of the work of the three researchers focused on human-jaguar conflict, a fair amount of that in the state of Cojedes.